Exploring optimism and pessimism in the Indian equity market. (8th June 2015) - Prosad, Jaya Mamta; Kapoor, Sujata; Sengupta, Jhumur
Abstract : Purpose: – The purpose of this paper is to capture the presence and impact of optimism in the Indian equity market. Design/methodology/approach: – The data set comprises the daily values of the Nifty 50 index, index options and Treasury-bill index for a period of five years (2006-2011). The focus of this paper is two pronged. It first investigates the presence of optimism (pessimism) using the pricing kernel technique suggested by Barone-Adesi et al. (2012). Second, it tries to analyze the relationship of this bias with stock market indicators like risk premium, market return and volatility using time series regression. Findings: – The findings indicate that the Indian equity market has been predominantly pessimistic from the period 2006 to 2011. The interaction of this bias with market indicators also unveils some interesting insights. The study shows that high past volatility can lead to pessimism in the Indian equity market and vice versa. It further explores that when the investors are rational, their risk and return relationship is positive while it tends to be negative when they are irrational. The impact of investors' irrationalities on asset valuation has also been accounted by Brown and Cliff (2005). Research limitations/implications: – The findings of the paper have significant implications for fund managers and asset management companies. It is recommended that they should try to identify behavioral biases in their clients before designing their portfolios. Originality/value: – This study is one of the very few attempts to capture the presence and impact optimism (pessimism) in the Indian equity market.